Evaluation of the recorded state mechanism for protecting agent integrity against malicious host - Abu Bakar, Kamalrulnizam (Agora University, 2008)
As agent technology is expected to become a possible base platform for an electronic services framework, especially in the area of Electronic Commerce, reliable security protection is a crucial aspect, since some transactions in this area might involve confidential information, such as credit card number, bank account information or some form of digital cash, that has value and might therefore be attacked. In addition, without proper and reliable security protection, the wide spread use of agent technology in real world applications could be impeded. In this paper, evaluation of the Recorded State Mechanism (RSM) previously proposed by the authors is presented. The evaluation examines the RSM security protection and implementation overhead, in order to analyse the RSM security strength and implementation feasibility in real world application.